REPRESENTASI SINGLE MOTHER DALAM VIDEO KLIP LAGU “NINA” KARYA FEAST ANALISIS SEMIOTIKA ROLAND BARTHES - Aliftia Ummi Nofitriasari (Sintesa, 2026)
Music videos serve not only as entertainment but also as a means of communication and a reflection of the social reality within society. “Nina” is a short film that depicts the life of a Single Mother as she faces various challenges and struggles alongside her children. The purpose of this study is to understand how the figure of the Single Mother is portrayed in the music video through Roland Barthes’s semiotic analysis. This study employs a qualitative approach using Roland Barthes’s semiotic analysis, which focuses on three levels of meaning: denotation, connotation, and myth. The data collection process was carried out through documentation of the “Nina” music video uploaded on YouTube. The data was analyzed by identifying visual cues that appeared in several areas relevant to the focus of the study. The findings show that the music video for the song “Nina” depicts Single Mothers as strong, responsible figures who have strong emotional bonds with their children. This representation is shown through various activities that demonstrate the attention, involvement, and emotional support given to children. Keywords: Representation, Single Mother, Music Video, Roland Barthes' Semiotics.